2022
DOI: 10.1088/1361-6668/ac6631
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-induced 2D superconductivity in a NbTiN film grown on Si by ultrahigh-vacuum magneton sputtering

Abstract: We report on the growth and characterization of a niobium titanium nitride (NbTiN) film on a Si substrate prepared by ultrahigh vacuum sputtering. We show that the superconducting transition temperature is lower than those of high-quality NbTiN films. Interestingly, even though the zero-temperature Ginzburg-Landau coherence length (=9.77 nm) is significantly shorter than the film thickness (=86 nm), we are still able to observe the Berezinskii-Kosterlitz-Thouless-like transition, indicating the two-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Preparation of the NbTiN Film: The detailed description regarding the preparation of the disordered nonstoichiometric 86-nm-thick NbTiN film is given in ref. [41]. In short, the film was deposited on a Si (100) substrate by the RF reactive magnetron co-sputtering from two separate NbN (99.5%) and TiN (99.5%) targets at 800 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparation of the NbTiN Film: The detailed description regarding the preparation of the disordered nonstoichiometric 86-nm-thick NbTiN film is given in ref. [41]. In short, the film was deposited on a Si (100) substrate by the RF reactive magnetron co-sputtering from two separate NbN (99.5%) and TiN (99.5%) targets at 800 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the preparation of the disordered nonstoichiometric 86‐nm‐thick NbTiN film can be found in ref. [ 41 ]. This film is deposited on a Si (100) substrate by radio frequency (RF) reactive magnetron co‐sputtering from two separate NbN and TiN targets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, experimental studies have shown that an overall reduction in I c is observed as wire lengths increase. , To realize high-performance superconducting devices, including SNSPDs with high detection efficiency and excellent temporal resolution, niobium-based nitrides are widely used materials . Previous studies have demonstrated that NbTiN, a ternary compound, exhibits considerable disorder that affects properties such as critical temperature ( T c ) and I c . In addition to microscopic parameters such as film thickness, grain sizes, and point defects, the Nb/Ti ratio can be adjusted to tune the composition of the material, which can have an impact on the superconducting properties and, ultimately, the performance of SNSPDs …”
Section: Introductionmentioning
confidence: 99%
“…This approach offers a valuable tool for characterizing and understanding the properties of atomically thin superconducting systems. On the other hand, Chen et al investigated the growth conditions and the properties of niobium titanium nitride films sputtered on silicon substrate [12]. Despite the film being three-dimensional (3D), the authors observe a Berezinskii-Kosterlitz-Thouless-like transition, indicating the presence of hidden two-dimensional (2D) superconducting properties.…”
mentioning
confidence: 99%